2022
DOI: 10.3390/ijerph19074186
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescriptions among Italian and Immigrant Pregnant Women Resident in Italy: A Cross-Sectional Population-Based Study

Abstract: Ensuring drug safety for pregnant women through prescription drug monitoring is essential. The aim of this study was to describe the prescription pattern of medicines among pregnant immigrant women from countries with high migratory pressure (HMPCs) compared to pregnant Italian women. The prevalence of drug prescriptions among the two study populations was analysed through record linkage procedures applied to the administrative databases of eight Italian regions, from 2016 to 2018. The overall prevalence of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The number of new users during the second and third trimesters increased from 1.1% to 2.0% for women with single pregnancies and from 0.7% to 1.8% for those with multiple pregnancies, then significantly reduced for both groups in the period following childbirth. Finally, we compared the consumption of antidiabetics between the Italian population and the subgroup of foreign women living in Italy, in particular women coming from developed countries and women coming from countries with a high migratory pressure level [35]. In the three populations analyzed, no differences were observed in the consumption of antidiabetics in the pre-pregnancy period; on the contrary, in the second and third trimester of pregnancy, foreign women showed a doubled proportion of use compared to Italians (second trimester: 1.8% vs. 0.9%; third trimester: 3.6% vs. 1.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of new users during the second and third trimesters increased from 1.1% to 2.0% for women with single pregnancies and from 0.7% to 1.8% for those with multiple pregnancies, then significantly reduced for both groups in the period following childbirth. Finally, we compared the consumption of antidiabetics between the Italian population and the subgroup of foreign women living in Italy, in particular women coming from developed countries and women coming from countries with a high migratory pressure level [35]. In the three populations analyzed, no differences were observed in the consumption of antidiabetics in the pre-pregnancy period; on the contrary, in the second and third trimester of pregnancy, foreign women showed a doubled proportion of use compared to Italians (second trimester: 1.8% vs. 0.9%; third trimester: 3.6% vs. 1.8%).…”
Section: Resultsmentioning
confidence: 99%
“…1 0.02 3 0.05 0 0.00 0 0.00 1 0.02 0 0.00 1 0.02 1 0.02 2 0.03 GLP-1 analogues 0 0.00 1 0.11 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 Glyphozines (alone or combined) 2 0.09 2 0.09 3 0.13 1 0.04 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 Gliptins (DDP-4 inhibitors alone or combined) 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 Insulins and analogues 14 0.17 14 0.17 13 0. 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 Repaglinide 1 0.05 1 0.05 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 0 0.00 Finally, we compared the consumption of antidiabetics between the Italian population and the subgroup of foreign women living in Italy, in particular women coming from developed countries and women coming from countries with a high migratory pressure level [35]. In the three populations analyzed, no differences were observed in the consumption of antidiabetics in the pre-pregnancy period; on the contrary, in the second and third trimester of pregnancy, foreign women showed a doubled proportion of use compared to Italians (second trimester: 1.8% vs. 0.9%; third trimester: 3.6% vs. 1.8%).…”
Section: Resultsmentioning
confidence: 99%
“… Overview on the different themes and specific papers discussed in this Special Issue [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. …”
Section: Figurementioning
confidence: 99%
“…D’Aloja et al reported on the prescription pattern of medicines among pregnant immigrant women from countries with high migratory pressure (HMPCs) compared to pregnant Italian women. As the migratory phenomenon represents a structural element of society, it is hereby reassuring that the prescription patterns only showed minor differences between both groups, while inappropriate prescription (antihypertensives, statins, anti-inflammatory drugs) was limited in both groups [ 13 ]. Two other papers focused on another ‘intercurrent’ event (the COVID-19 pandemic) and its effects on medicines utilization in pregnant and breastfeeding women in different European countries [ 14 , 15 ].…”
mentioning
confidence: 99%
“…Research on drug utilization during pregnancy has shown that up to 27-99% of pregnant women take at least one medication if also considering the consumption of vitamins and minerals, with a substantial number of drugs with a hazardous risk profile [5]. In Italy, automated databases have been used to investigate drug utilization in Pharmacoepidemiology 2023, 2 250 pregnancy, providing detailed prescription information collected prospectively for large cohorts of pregnant women from different regions [6][7][8][9]. In 2020, for the first time, the Italian Medicines Agency (AIFA) published a report based on the linkage record of different regional health information flows [10,11].…”
Section: Introductionmentioning
confidence: 99%